Scoping protocol review: PRISMA-ScR guide refinement - Samuel Miranda Mattos; Virna Ribeiro Feitosa Cestari; Thereza Maria Magalhães Moreira (Revista de Enfermagem da UFPI)
Objective: To clarify information about the PRISMA-ScR checklist and provide detailed guidance on items for improvement of the scoping review protocol. Methods: Literature review, with analysis of studies related to the topic, via the PubMed portal and the Joanna Briggs Institute website, in August 2022. A synthesis of the findings and recommendations for refinement of the method description were performed. Results: The analyzed material enabled the elaboration of recommendations for improvement of the protocol in seven items of PRISMA-ScR: Title, Summary, Objectives, Research, Selection of sources of evidence, Summary of results, and Expected results. Conclusion: By highlighting and clarifying the phases of the construction of the scoping review protocol, based on PRISMA ScR, we obtained the construction of a transparent and reproducible model.